2011
DOI: 10.2220/biomedres.32.167
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-cells are generated by neogenesis from non-β-cells after birth

Abstract: The mass of pancreatic β-cells is maintained throughout lifetime to control blood glucose levels. Although the major mechanism of the maintenance of β-cell mass after birth is thought to be selfreplication of pre-existing β-cells, it is possible that pancreatic β-cells are also generated from non-β-cells. Here, we address this issue by using the inducible Cre/loxP system to trace β-cells. We generated Ins2-CreERT2/R26R-YFP double knock-in mice, in which pancreatic β-cells can be labeled specifically and perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…These levels of Ngn3 mRNA in β cells (green and yellow cells) are higher than might be expected for cells in an adult pancreas, but are consistent with reports of NGN3 immunostaining in adult β cells (25,(33)(34)(35). Our findings of the absence of yellow cells in the pancreas after P5 suggest that β cell neogenesis does not occur after the early postnatal period (36).…”
Section: Introductionsupporting
confidence: 91%
“…These levels of Ngn3 mRNA in β cells (green and yellow cells) are higher than might be expected for cells in an adult pancreas, but are consistent with reports of NGN3 immunostaining in adult β cells (25,(33)(34)(35). Our findings of the absence of yellow cells in the pancreas after P5 suggest that β cell neogenesis does not occur after the early postnatal period (36).…”
Section: Introductionsupporting
confidence: 91%
“…alpha or delta cells) and mesenchymal stromal cells from bone marrow have been identified as beta cell precursors [30]. In contrast, lineage-tracing studies in mice show that only the beta cell itself serves as a beta cell source through self-duplication [31], although this was recently not confirmed [32] and is challenged by the fact that alpha cells [33,34], acinar cells [35,36] and ductal cells [37] are also sources for new beta cell formation, the last of which has been confirmed in the current study. Another source of beta cells is facultative progenitors in regenerating pancreatic ducts [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the negative result in Dor et al may be caused by their failure to examine the neonatal period or the new lobes after pancreatectomy (see below). Using the same approach, Nakamura et al recently examined the neonatal period and reported that neogenesis occurred in the second to third week after birth, but not in adults [21].…”
Section: Abbreviationsmentioning
confidence: 99%